Development of Stable Homozygous Wheat/Amblyopyrum muticum (Aegilops mutica) Introgression Lines and Their Cytogenetic and Molecular Characterization - King, Julie; Newell, Claire; Grewal, Surbhi; Hubbart-Edwards, Stella; Yang, Cai-yun; Scholefield, Duncan; Ashling, Stephen; Stride, Alex; King, Ian P. (Frontiers in Plant Science, 2019)
Wheat is one of the world’s most important sources of food. However, due to its evolution its genetic base has narrowed, which is severely limiting the ability of breeders to develop new higher yielding varieties that can adapt to the changing environment. In contrast to wheat, its wild relatives provide a vast reservoir of genetic variability for most, if not all, agronomically important traits. Genetic variation has previously been transferred to wheat from one of its wild relatives, Ambylopyrum muticum (previously known as Aegilops mutica). However, before the genetic variation available in this species can be assessed and exploited in breeding and for research, the transmission of the chromosome segments introgressed into wheat must first be stabilized. In this paper we describe the generation of 66 stably inherited homozygous wheat/Am. muticum introgression lines using a doubled haploid procedure. The characterisation and stability of each of these lines was determined via genomic in situ hybridization and SNP analysis. While most of the doubled haploid lines were found to carry only single introgressions, six lines carried two. Three lines carried only complete Am. muticum chromosomes, 43 carried only small or very small introgressions and the remainder carried either only large introgressions or a large plus a small introgression. The strategy that we are employing for the distribution and exploitation of the genetic variation from Am. muticum and a range of other species is discussed.